International public administrations in global public policy sources and effects of bureaucratic influence - Knill, Christoph; Steinebach, Yves 1987- (Routledge studies in policy and power, 2023)
"This book examines the rise and agency of International Organizations (IOs) and their bureaucratic bodies - the International Public Administrations (IPAs) - as a reflection of an ongoing transfer of political authority and power from the domestic to the international level. It shows that IPAs represent actors per se, with autonomy and resources that allow them to exert an independent influence on global policy-making processes and outputs. Providing a combination of novel conceptual lenses and research design to capture IPAs as an empirical phenomenon, the book takes an open, theoretically and methodologically diverse approach to show that IPAs are far from being negligible actors in global public policy and must be taken seriously as actors in policy-making beyond the nation state. This book will be of key interest to students, scholars and practitioners in Public Policy and Public Administration, International Relations, International Political Economy, as well as Organizational Studies"--